Dampak Urbanisasi terhadap Kehidupan Sosial-Ekonomi Desa - Nurmiati Nurmiati; Abd Haris (Lembaga Pengembangan Kinerja Dosen, 2024)
Urbanization is a social phenomenon that continues to increase and has a major impact on rural communities. This study aims to examine the impact of urbanization on the social and economic life of the Puncak village community. The study was conducted using a qualitative approach and case study method in Puncak Village with data collection techniques through in-depth interviews, observations, and documentation studies. The sample in this study was the Village Head, Communities who carried out urbanization in various regions and community leaders. Based on this study, the author can conclude that the impacts that occur in society due to the influence of urbanization include; increasing income used by urbanists to build houses, buy land for assets, provide assistance to the community for self-reliance. Universally, urbanization has a positive impact on the lives of urbanists, although some urbanists are unable to survive and choose to return to the Village.